Did COVID‐19 change life insurance offerings?. Issue 4 (4th June 2021) - Harris, Timothy F.; Yelowitz, Aaron; Courtemanche, Charles
Abstract: The profitability of life insurance offerings is contingent on accurate projections and pricing of mortality risk. The COVID‐19 pandemic created significant uncertainty, with dire mortality predictions from early forecasts resulting in widespread government intervention and greater individual precaution that reduced the projected death toll. We analyze how life insurance companies changed pricing and offerings in response to COVID‐19 using monthly data on term life insurance policies from Compulife. We estimate event‐study models that exploit well‐established variation in the COVID‐19 mortality rate based on age and underlying health status. Despite the increase in mortality risk and significant uncertainty, the results generally indicate that life insurance companies did not increase premiums or decrease policy offerings due to COVID‐19. Nonetheless, we find some evidence that premiums differentially increased for individuals with very high risk and that some policies were removed for the oldest of the old.